A natural drug entry channel in the ferritin nanocage. (December 2020) - Jiang, Bing; Chen, Xuehui; Sun, Guoming; Chen, Xiangru; Yin, Yufang; Jin, Yiliang; Mi, Qian; Ma, Long; Yang, Yili; Yan, Xiyun; Fan, Kelong
Graphical abstract: Highlights: A thermal-responsive drug entry channel in the H-ferritin nanocage is identified based on crystal structure and protein mutation analyses. A mild channel-based drug loading strategy that avoids the denaturization of HFn protein cage with denaturing agents is developed. Loading doxorubicin into HFn nanocage by the channel-based method significantly increases drug loading capacity and HFn recovery rate. Channel-based strategy produced HFn-Dox exhibits increased stability, better biosafety, and enhanced antitumor action than other methods. The drug entry channel is also accessible by multiple small molecule anticancer drugs. Abstract: Ferritin, a widely expressed iron binding protein, has emerged as a promising drug delivery vehicle due to its unique architecture, intrinsic tumor targeting property, and excellent biocompatibility. However, the translation studies of ferritin drug carrier are impeded by the low efficiency and low yield of the drug loading process, which typically employed Urea and pH dependent dis-assembly/reassembly methods. Here, based on crystal structure and protein mutation analyses, we identified a natural drug entry channel existed on the shell of recombinant human H-ferritin (HFn). Moreover, the opening state of this drug entry channel is sensitive to temperature changes. Based on these findings, we develop a simple channel-based drug loading strategy that avoids the denaturation of HFn protein cage with denaturing agents. Loading doxorubicin (Dox) into the HFn protein cage (HFn-Dox) by the channel-based strategy yields significantly higher drug loading efficiency, increased HFn recovery rate, and better stability than that of the denaturation-based methods. Importantly, animal experiments showed that the channel-loaded HFn-Dox had excellent biosafety and significantly improved antitumor activity when compared with the HFn-Dox prepared by the denaturation-based methods. We also found that the drug entry channel appears unique for HFn protein cage and is accessible to multiple small molecule anticancer drugs. Thus, the drug entry channel of HFn protein cage identified in this study provides a novel and highly effective drug loading approach for preparing HFn-drug formulations, which will greatly facilitate the translational study of ferritin drug carriers in cancer-targeting therapies.